Infection rates following initial cerebrospinal fluid shunt placement across pediatric hospitals in the United States - Simon, Tamara D. (2009)
OBJECT: Reported rates of CSF shunt infection vary widely across studies. The study objective was to determine the CSF shunt infection rates after initial shunt placement at multiple US pediatric hospitals. The authors hypothesized that infection rates between hospitals would vary widely even after adjustment for patient, hospital, and surgeon factors. METHODS: This retrospective cohort study included children 0–18 years of age with uncomplicated initial CSF shunt placement performed between January 1, 2001, and December 31, 2005, and recorded in the Pediatric Health Information System (PHIS) longitudinal administrative database from 41 children's hospitals. For each child with 24 months of follow-up, subsequent CSF shunt infections and procedures were determined. RESULTS: The PHIS database included 7071 children with uncomplicated initial CSF shunt placement during this time period. During the 24 months of follow-up, these patients had a total of 825 shunt infections and 4434 subsequent shunt procedures. Overall unadjusted 24-month CSF shunt infection rates were 11.7% per patient and 7.2% per procedure. Unadjusted 24-month cumulative incidence rates for each hospital ranged from 4.1 to 20.5% per patient and 2.5–12.3% per procedure. Factors significantly associated with infection (p < 0.05) included young age, female sex, African-American race, public insurance, etiology of intraventricular hemorrhage, respiratory complex chronic condition, subsequent revision procedures, hospital volume, and surgeon case volume. Malignant lesions and trauma as etiologies were protective. Infection rates for each hospital adjusted for these factors decreased to 8.8–12.8% per patient and 1.4–5.3% per procedure. CONCLUSIONS: Infections developed in > 11% of children who underwent uncomplicated initial CSF shunt placements within 24 months. Patient, hospital, and surgeon factors contributed somewhat to the wide variation in CSF shunt infection rates across hospitals. Additional factors may contribute to variation in CSF shunt infection rates between centers, but further study is needed. Benchmarking and future prospective multicenter studies of CSF shunt infection will need to incorporate these and other patient, hospital, and surgeon factors.